Analisis Penggunaan Istilah Geografi Dalam Berita Alam Di Surat Kabar Harian Kompas - Betaria Sihaloho; Annisya Agustina; Bintang Purba; Mhd Asa Arzaki Muiz; Tri Indah Prasasti (PT. Pustaka Cendekia Publisher, 2025)
The text discusses the significance of geographic terminology in mass media reporting, particularly in daily newspapers like Kompas. The accurate use of geographic terms plays a crucial role in conveying information about natural phenomena to the public. Properly used geographic terminology not only enhances the accuracy of news but also influences public understanding of natural events and disasters. The research aims to analyze the accuracy level of geographic terminology used in environmental news in Kompas and its impact on public literacy. Using a qualitative content analysis approach, the study identifies the geographic terms employed in news articles and interprets their meanings. The findings indicate that accurate use of geographic terminology can improve public literacy, enabling a better understanding of the context of natural phenomena and better preparedness for disasters.